PERANCANGAN TEMA POSTER PROMOSI PERTUNJUKAN BAND VIERRATALE DALAM POSTINGAN INSTAGRAM DI BULAN MEI 2022 - Agus darmawan Agus (UNIVERSITAS NUSA PUTRA, 2023)
Music is a universal of art, music is a way to communicate and interact between living things,. . While the poster is a medium that is expected to motivate the behavior of people who see it. . This thesis discusses the design of the promotional poster theme for the performance by the band Vierratale which combines elements of music and posters, both of which are trying to be translated into posts on Instagram. Therefore, this study refers to the influence of the genre of music and its characteristics on the poster illustration which produces a visual form of the influence of the music itself. The band that is the object of this poster's research is the band Vierratale from Jakarta, which is a genre of alternative pop music with fairytale nuances. This study aims to analyze Vierratale Instagram post posters. As well as to describe the characteristics of the poster illustration design. So that the public can know and be interested in the musical works of Vierratale and the visuals that the band displays in their performance posters. This study uses both design theory and other theories related to poster research. This study uses a qualitative method that presents descriptive data from the Vierratale show poster in May 2022 and the information is continuous with the theory and literature used.